Cover Feature: A One‐Step Germole to Silole Transformation and a Stable Isomer of a Disilabenzene (Chem. Eur. J. 4/2018). Issue 4 (2nd November 2017) - Reinhold, Crispin R. W.; Dong, Zhaowen; Winkler, Jan M.; Steinert, Henning; Schmidtmann, Marc; Müller, Thomas
Abstract : An unprecedented germole to silole transformation opened the way for the synthesis of novel silylenes based on a bicyclohexene skeleton, so‐called BCH silylenes. The astonishing stability of BCH silylenes results from homoconjugation between the dicoordinated Si atom and a remote C=C bond. This stabilization is more efficient than conventional electron delocalization, indicated by the fact that BCH silylenes are stable derivatives of the global minimum of the C4 Si2 H6 potential energy surface. More information can be found in the Full Paper by T. Müller et al. onpage 848 .